Intraocular inflammation after intravitreal injection of aflibercept 8 mg for treatment-refractory neovascular age-related macular degeneration: a case report - Nozomu Hashiya; Ichiro Maruko; Yuri Miyaguchi; Ruka Maruko; Taiji Hasegawa; Tomohiro Iida (BMC Ophthalmology)
Abstract Background To report a case of intraocular inflammation (IOI) after intravitreal injection of aflibercept 8 mg for treatment-refractory neovascular age-related macular degeneration. Case presentation An 80-year-old man with diabetes mellitus had neovascular age-related macular degeneration refractory to treatment with aflibercept 2 mg. Despite ten injections of faricimab, the exudation remained, and we switched to brolucizumab, which resulted in a mild IOI. The IOI improved with only topical steroids, and we switched back to aflibercept 2 mg for the exudation. However, the exudation remained, and we decided to switch to aflibercept 8 mg after careful discussion with the patient. Two weeks later, he experienced minor ocular pain and photophobia. One month later, although a dry macula was achieved, severe visual impairment occurred due to anterior chamber inflammation, retinal vasculitis, and retinal vascular occlusion. We diagnosed the severe IOI following aflibercept 8 mg and immediately started steroid eye drops and a sub-Tenon injection of triamcinolone acetonide. Although the inflammation resolved, his visual acuity did not improve. Conclusions This case demonstrated a potential dose-dependent inflammatory response following aflibercept 8 mg, which did not occur with aflibercept 2 mg in patients with a history of intraocular inflammation.